Pengaruh Konflik Kepentingan, Kualitas Audit, Leverage, dan Profitabilitas terhadap Konservatisme Akuntansi - Dwi Urip Wardoyo; Dea Khusnul Khotimah; Khanasya Ismy Lutfiany (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Accounting conservatism is a prudential principle by accountants in preparing financial statements. This is need to be implemented by the company for prevention from management's opportunistic behavior. Phenomena recognition of receivables as income by PT Garuda Indonesia, resulting in overstated profits are the case regarding accounting conservatism. Hasty to recognize receivables as revenue will raise the risk of uncollectible accounts and cause losses. Management's opportunistic can be reduced by applying accounting conservatism. The principle of conservatism is historically still relevant and can avoid the risks that may occur. The aims of this research are to examine the effect of conflict interest, audit quality, leverage and profitability to accounting conservatism. The populations in this study are companies in Kompas100 index listed on IDX within period 2018-2020. This is quantitative research with a purposive sampling technique. The analysis technique used in this study is panel data regression analysis through the Eviews 10. Hypothesis of this study is conflict of interest, audit quality, leverage, and profitability simultaneously affect accounting conservatism. Partially, conflict of interest, audit quality, and profitability has a significant positive effect on accounting conservatism, leverage has a significant negative effect on accounting conservatism.